Evaluation of feeding Indigofera zollingeriana leaf meal and Sardinella lemuru fish oil on lipids metabolism of local ducks - Arini, N.M.J.; Sumiati, S.; Mutia, R. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
The objective of this study was to evaluate the effectiveness usage of Indigofera zollingeriana leaf meal (I) and Sardinella lemuru fish oil (L) in diets on the decreasing levels of cholesterol and lipid metabolism of laying duck. One hundred and forty-four Magelang ducks aged 20-32 weeks, laying periode, with an average body weigth of 1,72±0,12 kg were used, which were divided into 6 groups of experimental diets, 3 replications, and of 8 layers each. A completely randomized design, 3x2 factorial design was used in this experiment. The first factor was usage Indigofera zollingeriana leaf meal which replaced protein soybean meal (0%, 5,5%, 11%). The second factor was usage Sardinella lemuru fish oil (0%, 2%). The results showed that the treatment (I5.5L2) was highly significant affected (P<0.01) the level of triglyceride, HDL, and LDL in the blood. The treatment I0L2 significantly decrease (P<0.05) total cholesterol of blood lipid profile and meat cholesterol. The treatment (I11L2) was highly significantly decreased (P<0.01) egg cholesterol. The conclusion of this study was that feeding Indigofera zollingeriana leaf meal 5.5% and Sardinella lemuru fish oil 2% in laying duck’s diet could maintain the balance of blood lipid profiles by lowering plasma triglycerides, LDL, cholesterol and raising up plasma HDL and plays an important role on lipid metabolism of Magelang laying ducks to produce eggs and meat with low cholesterol content.